THE ROLE OF SALIVARY IMMUNOGLOBULIN A IN THE PREVENTION OF THE UPPER RESPIRATORY TRACT INFECTIONS IN ATHLETES - AN OVERVIEW - Joanna Orysiak; Jadwiga Malczewska-Lenczowska; Zbigniew Szyguła; Andrzej Pokrywka (Termedia Publishing House, 2012)
Athletes subjected to high work loads may experience temporary suppression of the functions in the immune system which increases the susceptibility to infections of such subjects. Namely, upper respiratory tract infections (URTI) are the most common disorders among individuals subjected to high work loads and that issue is of utmost importance for sport immunologists. So far, no simple explanation has been offered as to the specific roles of detailed elements of the immune system in URTI incidence. One of the most likely markers is supposed to be the secretory immunoglobulin A (sIgA), associated with mucosal membranes of upper respiratory  tracts, although the results are far from being unequivocal yet. The most important results published in that area were discussed in this paper.